The Implementation Of Visual Media In Teaching English Literacy To The Deaf Students Of Tenth Grade At Smalb 1 Pangkep - Jusmaniar N; Endang Ruswiyani; Zari Indriyani Muin (Journal of Research and Multidisciplinary, 2022)
This research is about implementing visual media in teaching English literacy to deaf students who find difficulties in English literacy namely writing skills and reading skills. The objective of this research is (1) to implement the visual aid as a teaching medium in English literacy for the deaf student (2) to describe the English literacy teaching and learning process of deaf students by using visual media (pictures and videos). English literacy in this research refers to reading comprehension and writing skills. This study applied Classroom Action Research, which was carried out in two cycles. The subjects were three deaf students in tenth grade at SMALB 1 Pangkep (Senior High School level). The researchers used worksheets, tests, and observation in collecting data. The results of the observations and the final tests found that overall, students’ answers were ‘good’ in both reading and writing. This is proved by the student's score which passes the KKM = 70 (Minimum Completion Criteria Indicator). By facilitating students with visual media (pictures and videos), they are more active and interested in learning English.